Psychopathological correlates of polyvictimization in young offenders - Alvarez-Lister, María Soledad (Criminal justice and behavior, 2016)
Previous research has demonstrated a significant relationship between victimization and involvement in delinquency, but few studies have focused on exploring the effects of victimization on young offenders. This study analyzed the relationship between accumulated experiences of victimization, or polyvictimization, and the presence of psychopathology in 100 Spanish offenders (81% males) aged 14 to 17 years (M = 16.08, SD = 0.99). By means of cluster analysis, three groups of polyvictimized and two groups of less victimized offenders were identified. After controlling for demographic and criminal characteristics, polyvictims were more likely to reach a clinical level (T ≥ 65) of externalizing behavior (odds ratio [OR] = 3.136) and general impairment (OR = 2.878) than the remaining adolescents. These results showed that assessing multiple and less common forms of victimization is an important task when evaluating adolescent offenders, as polyvictimization is highly prevalent and places young people at a high risk of psychological impairment.